VERBA DALAM BAHASA ANAKALANG - Alex Djawa Alex; Simon Sabon Ola; Felysianus Sanga (Pendidikan Bahasa dan Sastra Indonesia Universitas Nusa Cendana, 2020)
Verbs are one of the word classes in the word class. All languages ​​in the world have a class of words 'verbs', apart from, nouns, adjectives and conjunctions. Verbs have the characteristics of (1) morphological form, (2) syntactic behavior, and (3) semantic behavior. In the Anakalang language, verbs are found based on morphological characteristics, such as: dana angu 'do not eat', syntactic features, such as' Jiangu na payapame ta loku '' The fish that we caught in the river. And semantic features, such as the use of the prefix pa- in a word, the meaning is determined by the use of the word in the sentence, not on the word obtained by the pa- prefix, such as: papalume which is formed from two words hammer and prefix pa- dan me which means' we